2001
DOI: 10.1001/jama.285.21.2729
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol and Ischemic Stroke in the Elderly

Abstract: TROKE IS A MAJOR CAUSE OF death and disability in the United States and is a growing public health concern. The latest projections estimate that more than 1 million strokes will occur every year by the year 2010. Moreover, stroke has a disproportionate impact on elderly, black, and Hispanic persons, who are among the fastest growing segments of the US population. Many studies have provided strong evidence for lipids as a risk factor for coronary artery disease (CAD). These studies demonstrate a direct relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
197
7
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(227 citation statements)
references
References 57 publications
16
197
7
7
Order By: Relevance
“…NOMAFS is a cohort of high-risk Caribbean-Hispanic probands and their family members initially identified from the Northern Manhattan Study (NOMAS) stroke-free cohort [27]. A high-risk proband was defined by one of the following criteria: (1) reporting a sibling with a history of myocardial infarction or stroke; (2) having two of three quantitative risk phenotypes (maximal carotid plaque thickness, left ventricle mass divided by the body surface area, or homocysteine level) above the 75th percentile in the NOMAS cohort.…”
Section: Study Subjectsmentioning
confidence: 99%
“…NOMAFS is a cohort of high-risk Caribbean-Hispanic probands and their family members initially identified from the Northern Manhattan Study (NOMAS) stroke-free cohort [27]. A high-risk proband was defined by one of the following criteria: (1) reporting a sibling with a history of myocardial infarction or stroke; (2) having two of three quantitative risk phenotypes (maximal carotid plaque thickness, left ventricle mass divided by the body surface area, or homocysteine level) above the 75th percentile in the NOMAS cohort.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Крупные исследования со статинами показали значительное снижение частоты развития инсульта у пациентов с ИБС или с высоким риском за счет снижения частоты развития ишемиче-ского инсульта [469] . Повышенные концентрации три-глицеридов и низкие уровни ХС-ЛПВП также связаны с негеморрагическим инсультом [490,491] . Именно поэтому пациенты с ишемическим цереброваскуляр-ным заболеванием заслуживают таково же внимания к медикаментозному контролю липидов крови, как и больные ИБС .…”
Section: профилактика инсультаunclassified
“…Based on the observation that low HDL cholesterol levels were associated with cerebrovascular events (Sacco et al 2001;Wannamethee et al 2000), Paterno et al showed that pretreatment with reconstituted HDL reduced neuronal damage in two experimental models of stroke in rats (Paterno et al 2004). They showed that high doses of rHDLs (120 mg/kg) infused 2 h before the onset of stroke reduced the brain necrotic area by 61 and 76 %, respectively, in an excitotoxic (NMDA) and a transient MCAO model of stroke in rats.…”
Section: Hdls and Acute Stroke: Experimental Modelsmentioning
confidence: 99%